2019
DOI: 10.1063/1.5092372
|View full text |Cite
|
Sign up to set email alerts
|

3D nanoprinting via focused electron beams

Abstract: Additive manufacturing of three-dimensional objects on the nanoscale is a very relevant topic but still a highly challenging task. Among the pool of nanofabrication techniques, focused electron beam induced deposition (FEBID) has recently developed from a trial-and-error laboratory method to a predictable 3D nanoprinting technology with unique advantages. This perspective article first introduces the basic principles of 3D-FEBID, followed by an overview of historical developments with a particular emphasis on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
148
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(149 citation statements)
references
References 92 publications
0
148
0
1
Order By: Relevance
“…Over the last few years, this has led to the evolution of a simulation-guided 3D computer aided design (CAD) approach which was pioneered by Fowlkes and collaborators [11] and has been further developed towards a reliable instrument for 3D nano-fabrication even of complex nano-architectures, as was recently reviewed by Winkler et al [12]. For the fields of 3D nano-magnetism and nano-superconductivity, the precursors Co 2 (CO) 8 [1], Fe 2 (CO) 9 [13], HCo 3 Fe(CO) 12 [3] (FEBID), W(CO) 6 [14], and Nb(NMe 3 ) 2 (N-t-Bu) [7] (FIBID) have been used and proven to be particularly suited. With a view to the simulation-guided 3D CAD approach to nano-fabrication which uses the continuum model of FEBID/FIBID growth, a set of simulation parameters is required; see Reference [15] for a recent review.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few years, this has led to the evolution of a simulation-guided 3D computer aided design (CAD) approach which was pioneered by Fowlkes and collaborators [11] and has been further developed towards a reliable instrument for 3D nano-fabrication even of complex nano-architectures, as was recently reviewed by Winkler et al [12]. For the fields of 3D nano-magnetism and nano-superconductivity, the precursors Co 2 (CO) 8 [1], Fe 2 (CO) 9 [13], HCo 3 Fe(CO) 12 [3] (FEBID), W(CO) 6 [14], and Nb(NMe 3 ) 2 (N-t-Bu) [7] (FIBID) have been used and proven to be particularly suited. With a view to the simulation-guided 3D CAD approach to nano-fabrication which uses the continuum model of FEBID/FIBID growth, a set of simulation parameters is required; see Reference [15] for a recent review.…”
Section: Introductionmentioning
confidence: 99%
“…With a view to the simulation-guided 3D CAD approach to nano-fabrication which uses the continuum model of FEBID/FIBID growth, a set of simulation parameters is required; see Reference [15] for a recent review. Here, we focus on the precursors HCo 3 Fe(CO) 12 and Nb(NMe 3 ) 2 (N-t-Bu), recently introduced by us, and provide the activation energies and pre-exponential factors for thermally induced precursor desorption from a series of FEBID experiments performed under low beam current conditions (I = 30 pA) on Si(100)/SiO 2 substrates held at different temperatures between 5 • C and 24 • C. By comparison with deposition results obtained under high beam current conditions (I = 1.6 nA), we highlight the morphological consequences imposed by the change of the growth regime from reaction-rate limited or diffusion enhanced to mass-transport limited. We note that similar experiments with FIBID, as would seem to be natural for the Nb-precursor, cannot be done for deduction of the activation energies due to the unavoidable etching effect in parallel to the growth; see Reference [15] for details.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 These works make an important step towards controllable nanoscale 3D printing of networks of nanowires, correcting effectively for various phenomena present in FEBID when growing pseudo-1D elements using different approaches. 12 To exploit the full potential of FEBID as a 3D fabrication tool, however, the nanoprinting protocol needs to be redefined in order to generalize it to more complex geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have demonstrated that focused electron beam induced processing (FEBIP) has high potential for the controlled bottom-up fabrication of metallic 3D nanostructures [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Furthermore, the basic processes during FEBIP are understood to more and more detail leading to developments towards more diverse, cleaner and more defined deposits for various potential applications [7,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Dissociation is generated mainly by low-and medium-energy secondary or backscattered electrons which have a high interaction cross-section with matter. Depending on the substrate and the chemical composition of the targeted nanostructure, several in-situ and ex-situ cleaning procedures have been developed [14,19,20].…”
Section: Introductionmentioning
confidence: 99%